The assessment of reading difficulties - Ocampo, Dina (2006)
This paper addresses the assessment of reading difficulties in terms of the three clusters of factors that influence reading performance - reader, text, and context. Guidelines for assessment of various types of reading difficulties are given, and formal as well as formal measures are described. It also calls attention to the role of instruction, suggesting that poor teaching, more often than not, is the cause of reading difficulties.
Keywords: Reading comprehension -- Ability testing; Reading